A data privacy protection scheme for Internet of things based on blockchain. Issue 5 (9th July 2020) - Gong, Jing; Mei, Yurong; Xiang, Feng; Hong, Hanshu; Sun, Yibo; Sun, Zhixin
Abstract: In recent years, the Internet of things (IoT) equipment has grown rapidly, and the scale of the IoT has also expanded. The IoT is deployed in the system in a centralized manner. At the same time that massive data has put a certain amount of pressure on the storage, the open network environment has not fully protected the privacy of the IoT data, which has become one of the important factors restricting the development of the IoT. Blockchain is a point‐to‐point distributed ledger technology based on cryptographic algorithms. The characteristics of decentralization, tamper resistance, anonymity, and public verifiability can alleviate data security issues in IoT. Ring signature and proxy reencryption are common encryption technologies in the field of privacy protection. Therefore, this article combines blockchain technology with ring signature and proxy reencryption to propose a privacy protection solution for the IoT. Through this solution, the data authorized for sharing in the IoT is transmitted in the system in the form of ciphertext, the identity information of the data sender is protected, and the distributed ledger eases the pressure of mass data storage on a centralized server. The correctness and safety of the proposed scheme are also analyzed. Abstract : This article combines blockchain technology with ring signature and proxy reencryption to propose a privacy protection solution for the Internet of things. Through this solution, the data authorized for sharing in the Internet of things is transmitted in the system in the form of ciphertext, the identity information of the data sender is protected, and the distributed ledger eases the pressure of mass data storage on a centralized server.